VIRTUAL COMMUNITIES OF PRACTICE MULTIPLE LITERACY - Daniela Melaré Varros; María García Pérez Calabuig (Ediciones Universidad de Salamanca, 2010)
Technologies have transformed the way we interact with others. Are expanding the dimensions of the participatory process in digital environments such as educational settings, thanks to social networks for learning. At the present time have created new ways to communicate and learn, a group of social networks that facilitate the participation of all involved, and therefore are also tools of social learning. Communication possibilities expand educational dimensions in digital scenarios. Participation goes from being a chance to become the main source of teaching and learning collaborative. It is necessary to the review of pedagogical approaches and methodologies to create a scenario, which arises in the virtual mode. The challenge now is training and developing literacy skills through providing multiple virtual learning communities.